The Effect of Impeller Design on the Mixing of Non-Newtonian Internal Tyre Lubricant - Azoddein, A.A.; Ibrahim, S.; Hassan, A. (SIRIM Berhad, 2001)
Experiments were conducted to assess the performance of various classic, commercial and made-to-order impeller designs to mix a rheologically complex fluid of commercial value. This study highlights the importance of impeller-to-tank diameter ratio (D/T) and impeller geometry for optimal mixing results, based on the flow of fluid and impeller power requirement. Although an existing finned-paddle type impeller produced the desired final product, satisfactory results were also obtained with a commercial impeller of smaller D/T, which could lead to 80% power savings.